Proteomic Responses of Dark-Adapted Euglena gracilis and Bleached Mutant Against Light Stimuli - Chen, Zhenfan; Chen, Zixi; Zhu, Jiayi; He, Jiayi; Liu, Qiong; Zhu, Hui; Lei, Anping; Wang, Jiangxin (Frontiers in Bioengineering and Biotechnology, 2022)
Euglena gracilis (E. gracilis) has secondary endosymbiotic chloroplasts derived from ancient green algae. Its chloroplasts are easily lost under numerous conditions to become permanently bleached mutants. Green cells adapted in the dark contain undeveloped proplastids and they will develop into mature chloroplasts after 3 days of light exposure. Thus, E. gracilis is an ideal model species for a chloroplast development study. Previous studies about chloroplast development in E. gracilis focused on morphology and physiology, whereas few studies have addressed the regulatory processes induced by light in the proteome. In this study, the whole-genome proteome of dark-adapted E. gracilis (WT) and permanently ofloxacin-bleached mutant (B2) was compared under the light exposure after 0, 12, and 72 h. The results showed that the photosynthesis-related proteins were up-regulated over time in both WT and B2. The B2 strain, with losing functional chloroplasts, seemed to possess a complete photosynthetic function system. Both WT and B2 exhibited significant light responses with similar alternation patterns, suggesting the sensitive responses to light in proteomic levels. The main metabolic activities for the utilization of carbon and energy in WT were up-regulated, while the proteins with calcium ion binding, cell cycle, and non-photosynthetic carbon fixation were down-regulated in B2. This study confirmed light-induced chloroplast development in WT from dark, and also for the first time investigates the light responses of a bleached mutant B2, providing more information about the unknown functions of residual plastids in Euglena bleached mutants.